On Poetic Style of Bylinas - Mitropolskaja, N. (Literatūra, 1969)
The article presents some observations on the poetic style of bylinas. The objectivity of the poetic expression of epic heroics is revealed by the selection of events, situations and characteristics. The bylina image unites in itself objective situation and psychologization of the moment, action, emotional state of the hero and his environment. The epic method of portrayal, predominating in the bylina, assumes synonymous description of feelings, the subjective elements being subordinated to general dynamics of artistic narration and the idea of creating an integral picture of the ideal epic world.
Keywords: -